A nanoporous nickel-based intermetallic compound catalyst and preparation method thereof

By designing the combination of nickel-aluminum intermetallic compound phase and nickel phase, a nanoporous nickel-based intermetallic compound catalyst was prepared, which solved the problem of unstable and low selectivity of the Reney nickel catalyst in the air, achieving efficient 1,4 -Butyndiol hydrogenation reaction has significant catalytic stability and selectivity improvement.

CN116408087BActive Publication Date: 2024-12-31TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310529696.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-11
Publication Date
2024-12-31
Estimated Expiration
2043-05-11

AI Technical Summary

Technical Problem

The existing Rainey nickel catalysts are unstable in the air, have low catalytic selectivity and poor stability performance, making it difficult to meet the efficient preparation needs of 1,4-butyne glycol hydrogenation reaction.

Method used

By designing the coordination between the nickel-aluminum intermetallic compound phase and the nickel phase, a nanoporous nickel-based intermetallic compound catalyst was prepared, and the ratio of the Ni phase to the Ni2Al3 phase in the catalyst was adjusted to form a catalyst with a long-range ordered structure and excellent stability. Improve catalytic activity and selectivity.

Benefits of technology

The stability and catalytic activity of the catalyst are significantly improved, especially in the hydrogenation reaction of 1,4-butyne glycol, which has high selectivity and stability properties. The catalyst maintains good stability in the air and increases the surface area of ​​the catalyst to Enhance hydrogen adsorption capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004224137960000051
    Figure BDA0004224137960000051
  • Figure BDA0004224137960000061
    Figure BDA0004224137960000061
  • Figure HDA0004224137970000011
    Figure HDA0004224137970000011
Patent Text Reader

Abstract

The invention discloses a nanoporous nickel-based intermetallic compound catalyst, wherein the mass fraction of Ni in the catalyst is 64.1%-93.4%; the molar ratio of the Ni phase to the Ni2Al3 phase in the catalyst is 0.45-17.5. The catalyst of the invention has good catalytic activity and catalytic selectivity, and has good stability in air. The catalyst of the invention has a selectivity of not less than 98% for hydrogenating 1,4-butynediol to obtain 1,4-butanediol. The catalyst of the invention has good catalytic stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to a nanoporous nickel-based intermetallic compound catalyst and a preparation method thereof. Background Art

[0002] 1,4-Butanediol is an important basic organic raw material with high added value and wide application. It is often used in the fields of medicine, textiles, military industry, etc.

[0003] In the preparation process of 1,4-butanediol, the existing technology mainly obtains it through selective hydrogenation reaction on 1,4-butynediol. However, the hydrogenation of 1,4-butynediol is a complex reaction process. In addition to the target product 1,4-butanediol, there are also by-products such as n-butanol and 2-hydroxytetrahydrofuran. Therefore, it is of great significance to improve the selectivity of the catalyst used in the relevant process to the target product 1,4-butanediol.

[0004] Raney nickel (RaneyNi) catalyst is often used as a common catalyst for the hydrogenation of 1,4-butynediol to prepare 1,4-butanediol in industry because of its low price and high catalytic activity. However, there are certain technical problems with Raney nickel. First, Raney nickel is very unstable in the air and is easily oxidized and burned in the air, thereby losing the activity of the catalyst. Therefore, Raney nickel is often stored in water in the prior art, which brings great trouble to transportation and use; secondly, Raney nickel has relatively low selectivity in the reaction of hydrogenating 1,4-butynediol to prepare 1,4-butanediol compared to precious metals such as palladium and platinum; finally, the porous structure of Raney nickel catalyst has poor catalytic stability during catalytic use. In recent years, research on Raney nickel catalysts has mainly focused on improving the catalytic activity of Raney nickel by element doping. Summary of the invention

[0005] Based on the existing research, this case has obtained a Raney nickel catalyst with the structural characteristics of the phase intermetallic compound by compounding different nickel-aluminum intermetallic compound phases with the nickel phase through a large amount of research. While retaining the high activity of the traditional Raney nickel catalyst, it also has the long-range ordered structural characteristics of the intermetallic compound, and has the excellent stability and catalytic selectivity of the intermetallic compound, so that the catalyst has good stability in the air. We tested, compared and verified through a large number of experiments, and surprisingly found that the stability and catalytic activity of the catalyst of the present invention are significantly improved compared with Raney nickel, especially in the selectivity of the catalyst for the catalytic hydrogenation reaction of 1,4-butynediol and the catalytic stability of the catalyst. We further infer that it may be because the coordination between the nickel phase and the nickel-aluminum intermetallic compound phase in the catalyst directly leads to the completely different ordered crystal structure and surface metal atom arrangement in the final catalyst, which makes it have completely different stability and catalytic activity. We further speculate that whether different nickel-aluminum intermetallic compound phases and nickel phases are matched, the performance of the catalyst will also be different. For this reason, we have further designed different nickel-aluminum intermetallic compound phases and nickel phases to compare and verify our conjecture. It was found that the catalytic activity, stability, selectivity and catalytic stability of the catalyst are directly related to the nickel phase and nickel-aluminum intermetallic compound phase in the catalyst.

[0006] Based on the above-mentioned large number of experiments, we have further surprisingly found that when the catalyst has the same nickel phase and nickel-aluminum intermetallic compound phase, but the ratio of nickel phase to nickel-aluminum intermetallic compound phase is different, the performance of the catalyst will also be different. The experimental results are exciting. We believe that even if the nickel-aluminum intermetallic compound phase and nickel phase in the catalyst are the same, the completely different ratio between the nickel-aluminum intermetallic compound phase and the nickel phase will also cause the catalyst to obtain different catalytic activities.

[0007] We believe that all this may come from the differences in the crystal cell structures of the catalysts. How to obtain catalysts with better stability, catalytic activity and selectivity? What technical difficulties need to be overcome? Which types of nickel-aluminum intermetallic compound phases and nickel phases should be selected to cooperate with each other? On this basis, how to regulate the ratio between the selected nickel-aluminum intermetallic compound phase and the nickel phase? The key technology to solve these technical difficulties comes from the control of the preparation method and the conditions during the preparation process.

[0008] The present invention aims at the problems in the prior art and discloses a nanoporous nickel-based intermetallic compound catalyst and a preparation method thereof. The catalyst obtained by the present invention has good catalytic performance and selectivity for the hydrogenation of 1,4-butynediol, good stability in the air, and significant catalytic stability.

[0009] The present invention is realized by the following technical scheme: the present invention provides a nanoporous nickel-based metal compound catalyst, wherein the atomic percentage of Ni in the catalyst is 64.1%-93.4%; and the molar ratio of Ni phase to Ni2Al3 phase in the catalyst is 0.45-17.5.

[0010] The above-mentioned design of the present invention, in which the catalyst of the present invention is designed by designing the coordination of Ni phase and Ni2Al3 phase, and further designing the ratio of Ni phase to Ni2Al3 phase in the catalyst, thereby obtaining a catalyst with good catalytic performance and selectivity, and good stability in air.

[0011] As a further solution, the mass fraction of Ni in the catalyst is 68.5%-76.5%; the molar ratio of Ni phase to Ni2Al3 phase in the catalyst is 1-2.5.

[0012] As a further solution, the mass fraction of Ni in the precursor of the catalyst is 43.3%-55.0%.

[0013] As a further solution, the catalyst has a nanoporous structure, and the specific surface area of ​​the catalyst is 70m 2 / g-120m 2 / g. The catalyst with nanoporous structure can increase the surface area of ​​the catalyst, which is conducive to adsorbing more hydrogen, forming more active hydrogen, and improving the catalytic activity of the catalyst.

[0014] As a further solution, the average pore size of the nanoporous structure is 4 nm-30 nm.

[0015] As a further embodiment, the catalyst has characteristic XRD diffraction peaks at 18.1°, 25.3°, 31.2°, 45.6°, 48.6°, 65.3°, and 82.5°.

[0016] As a further embodiment, the selectivity of the catalyst for hydrogenating 1,4-butynediol to obtain 1,4-butanediol is not less than 98%.

[0017] The present invention also provides a method for preparing the catalyst, which comprises smelting pure nickel and pure aluminum to obtain a nickel-aluminum alloy ingot, vacuum spinning to obtain a nickel-aluminum alloy strip, obtaining a catalyst precursor, crushing to obtain a nickel-aluminum alloy powder, dealloying, washing, and drying to obtain the catalyst of the present invention. In the method of the present invention, the composition of the phase in the precursor can be adjusted by controlling the conditions in the preparation process, such as the spinning speed.

[0018] As a further solution, the mass fraction of Ni in the precursor of the catalyst is 43.3%-55.0%; the particle size of the nickel-aluminum alloy powder is 80 mesh-200 mesh; the dealloying solution is sodium hydroxide, and the concentration of the sodium hydroxide is 0.4M-0.6M; the dealloying time is 20min-120min. In the method of the present invention, the atomic ratio of Ni / Al in the catalyst precursor first selected directly affects the ratio between the nickel-aluminum intermetallic compound phase and the nickel phase in the final catalyst and the selection of the nickel-aluminum intermetallic compound phase. On the basis of obtaining the precursor of the catalyst within the scope of the present invention, the concentration of sodium hydroxide of a suitable concentration is selected, and the nickel-aluminum intermetallic compound phase outside the design of the present invention can be selectively removed, thereby designing the matching metal phase and nickel-aluminum intermetallic compound phase in the catalyst, and forming a loose porous structure at the same time.

[0019] As a further embodiment, the concentration of the sodium hydroxide is 0.6M.

[0020] As a further solution, the dealloying condition is at 20°C-30°C.

[0021] As a further solution, the best method of melting may be vacuum arc melting at a current of 250A.

[0022] As a further solution, the best way of crushing may be ball milling.

[0023] The characteristics and beneficial effects of the present invention are:

[0024] (1) The catalyst of the present invention has good catalytic performance and selectivity, and has good stability in air.

[0025] (2) The selectivity of the catalyst of the present invention for hydrogenating 1,4-butynediol to obtain 1,4-butanediol is not less than 98%.

[0026] (3) The catalyst of the present invention has good catalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the nanoporous nickel-based intermetallic compound catalyst in the embodiments of the present invention, the drawings required for use in the embodiments or the prior art description will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention.

[0028] Figure 1 The XRD diagrams of the precursor of the catalyst and the final catalyst obtained in Example 1 of the present invention.

[0029] Figure 2 It is the pore size distribution diagram of the catalyst of the present invention.

[0030] Figure 3 The XRD diagram of the catalyst of the present invention as the dealloying time increases.

[0031] Figure 4 The DSC diagrams of the catalyst of the present invention and the comparative example catalyst are shown in FIG.

[0032] Figure 5 It is the selectivity of the catalyst of the present invention to 1,4-butanediol at different catalytic times.

[0033] Figure 6 The selectivity of RaneyNi for 1,4-butanediol at different catalytic times is shown in the comparative example.

[0034] Figure 7 This is the selectivity of comparative example NP-Ni to 1,4-butanediol at different catalytic times.

[0035] Figure 8 This is a catalytic cycle experiment of the catalyst of the present invention.

[0036] Fig. 9 This is a catalytic cycle experiment of the comparative catalyst NiAl3-Ni.

[0037] Fig.10 The hydrogenation activity of different catalysts for phenylacetylene and 1,4-butynediol hydrogenation.

[0038] Fig.11 This is the XRD diagram of Comparative Example 2 during the preparation process.

[0039] Figure 12 is a LSV curve diagram, where a is the LSV curve diagram of NiAl3 under 0.6M sodium hydroxide; b is the LSV curve diagram of Ni2Al3 under 0.6M sodium hydroxide; c is the LSV curve diagram of Ni 31.5 Al 68.5 LSV curves of the alloy under different concentrations of sodium hydroxide. DETAILED DESCRIPTION

[0040] In order to facilitate understanding of the nanoporous nickel-based metal compound catalyst and its preparation method of the present invention, a nanoporous nickel-based metal compound catalyst and its preparation method of the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereto.

[0041] Example 1: Pure nickel and pure aluminum are used as raw materials for vacuum arc melting (current of 250A), and the smelted nickel-aluminum alloy ingot is vacuum stripped (rotation speed of 2000rpm) to obtain a nickel-aluminum alloy strip with a certain thickness, wherein the mass fraction of Ni in the catalyst precursor is 50%, and then the nickel-aluminum strip is ball-milled to obtain 80-200 mesh nickel-aluminum alloy powder. The dealloying alkali solution is 0.6M NaOH, the dealloying time is 20min, and the catalyst of the present invention is obtained after centrifugal washing and drying. Figure 1 This is the XRD pattern of the catalyst after dealloying for 20 min.

[0042] Example 2: Pure nickel and pure aluminum are used as raw materials for vacuum arc melting (current of 250A), and the smelted nickel-aluminum alloy ingot is vacuum stripped (rotation speed of 2000rpm) to obtain a nickel-aluminum alloy strip with a certain thickness, wherein the mass fraction of Ni in the catalyst precursor is 50%, and then the nickel-aluminum strip is ball-milled to obtain 80-200 mesh nickel-aluminum alloy powder. The dealloying alkali solution is 0.6M NaOH, and the dealloying time is 20min, 40min, 90min, and 120min. After centrifugal washing and drying, the catalyst of the present invention is obtained. Figure 3 These are the XRD patterns of the catalysts after dealloying for 20 min, 40 min, 90 min and 120 min.

[0043] Example 3: Pure nickel and pure aluminum were used as raw materials for vacuum arc melting (current of 250A), and the smelted nickel-aluminum alloy ingot was vacuum stripped (rotation speed of 2000rpm) to obtain a nickel-aluminum alloy strip with a certain thickness, wherein the mass fraction of Ni in the nickel-aluminum alloy precursor was 48.2%, and then the nickel-aluminum strip was ball milled to obtain 80-200 mesh nickel-aluminum alloy powder. The dealloying alkali solution was 0.6M NaOH, the dealloying time was 20min, and the catalyst of the present invention was obtained after centrifugal washing and drying.

[0044] Example 4: Pure nickel and pure aluminum were used as raw materials for vacuum arc melting (current of 250A), and the smelted nickel-aluminum alloy ingot was vacuum stripped (rotation speed of 2000rpm) to obtain a nickel-aluminum alloy strip with a certain thickness, wherein the mass fraction of Ni in the nickel-aluminum alloy precursor was 52.1%, and then the nickel-aluminum strip was ball milled to obtain 80-200 mesh nickel-aluminum alloy powder. The dealloying alkali solution was 0.6M NaOH, the dealloying time was 20min, and the catalyst of the present invention was obtained after centrifugal washing and drying.

[0045] Comparative Example 1: Commercially available Raney Ni catalyst.

[0046] Comparative Example 2: A catalyst having a nickel metal phase and a NiAl3 phase, the preparation method of which includes vacuum arc melting (current of 250A) with pure nickel and pure aluminum as raw materials, vacuum belt spinning (rotation speed of 2000rpm) of the smelted nickel-aluminum alloy ingot to obtain a nickel-aluminum alloy strip with a certain thickness, wherein the mass fraction of Ni in the nickel-aluminum alloy precursor is 19.5%, and then ball milling the nickel-aluminum strip to obtain 80-200 mesh nickel-aluminum alloy powder. The dealloying alkali solution is 0.6M NaOH, the dealloying time is 90min, and the catalyst is obtained after centrifugal washing and drying. The XRD of the catalyst prepared in Comparative Example 2 is Fig.11 shown.

[0047] Comparative Example 3: Catalyst Ni, represented by NP-Ni in the following figure, has a preparation method comprising vacuum arc melting (current of 250A) with pure nickel and pure aluminum as raw materials, vacuum belt spinning (rotation speed of 2000rpm) of the smelted nickel-aluminum alloy ingot to obtain a nickel-aluminum alloy strip with a certain thickness, wherein the mass fraction of Ni in the nickel-aluminum alloy precursor is 50%, and then ball milling the nickel-aluminum alloy strip to obtain 80-200 mesh nickel-aluminum alloy powder. The dealloying alkali solution is 2MNaOH, and the dealloying time is 5h.

[0048] Results and Analysis

[0049] Table 1 Selectivity of catalysts with different nickel-aluminum intermetallic compound phases

[0050]

[0051] Table 2 Comparison of catalytic performance of different ratios of nickel-aluminum intermetallic compound phase and nickel phase

[0052]

[0053] We successfully obtained a catalyst having the characteristics of an intermetallic compound with both Ni phase and Ni2Al3 phase through the method of the present invention. As shown in Example 1, we can Figure 1 It is verified by XRD that the catalyst of the present invention has both Ni phase and Ni2Al3 phase, and the catalyst of the present invention also has a nanoporous structure, such as Figure 2 As shown, Figure 2 It can be shown that the specific surface area of ​​the catalyst of the present invention is 80m 2 / g, the pore size distribution of the catalyst is concentrated in 4nm-8nm, the average pore size is 6nm, and the pore distribution is uniform. On this basis, alkaline solution is used for phase removal during the catalyst preparation process. Due to the poor crystallinity of the Ni phase, Figure 3 There is no obvious characteristic peak in Figure 3The figure mainly shows the phase change in the present invention. We can see that when the alkaline solution dealloying is not performed, the catalyst contains not only Ni2Al3 phase but also NiAl3 phase. When the dealloying time is 20 minutes, we successfully prepare the catalyst of the present invention, and the catalyst mainly contains Ni2Al3 phase and Ni phase.

[0054] On this basis, we first studied the differences between catalysts with intermetallic compound characteristics (Ni2Al3-Ni catalyst and NiAl3-Ni catalyst) and traditional Raney Ni catalyst and NP-Ni catalyst. Catalysts with intermetallic compound characteristics have better stability in air than Raney Ni catalyst and NP-Ni catalyst. Figure 4 In order to soak different catalysts with ethanol and put them into the instrument, nitrogen was used to blow away the ethanol on the surface of the catalyst and volatilize it. When the mass of the catalyst remained unchanged, air was introduced and the ambient temperature in the instrument was controlled at 30°C. The results are as follows Figure 4 As shown, Figure 4 The shaded area is the nitrogen purge process. We can Figure 4 It can be seen that the catalyst with intermetallic compounds has been in a stable state in the instrument, while the Raney Ni catalyst and NP-Ni catalyst spontaneously combusted in the instrument. Figure 4 The temperature of the Raney Ni catalyst and the NP-Ni catalyst will increase and then decrease. Since the Raney Ni catalyst and the NP-Ni catalyst react, the weight of the Raney Ni catalyst and the NP-Ni catalyst also changes. It can be seen that the catalyst with intermetallic compounds is more stable in the air than the Raney Ni catalyst and the NP-Ni catalyst.

[0055] Second, when the catalysts with intermetallic compound characteristics (Ni2Al3-Ni catalyst), Raney Ni catalyst, and NP-Ni catalyst were tested for the hydrogenation of 1,4-butynediol, the catalysts with intermetallic compound characteristics had higher selectivity and catalytic activity for 1,4-butynediol, such as Figure 5-Figure 7 As shown. Among them, from Figure 5 It can be seen that when the catalyst of the present invention is used for 60 minutes, 98.4% of 1,4-butynediol is converted into 1,4-butanediol; Figure 6 It can be seen that when the Raney Ni catalyst was used for 1440 minutes, only 94.2% of 1,4-butynediol was converted into 1,4-butanediol. Figure 7It can be seen from the NP-Ni catalyst that only 96% of 1,4-butynediol is converted into 1,4-butanediol at 1080 minutes of the NP-Ni catalyst. The comparison results show that the catalyst of the present invention has better catalytic activity and selectivity than the Raney Ni catalyst and the NP-Ni catalyst.

[0056] On this basis, we further discovered that even though they are all catalysts with intermetallic compound characteristics, due to the different combinations of the metal phase and the nickel-aluminum intermetallic compound phase in the catalyst, the specificity of the catalyst and the catalytic stability of the catalyst also have significant differences. Figure 8 and Fig. 9 It can be seen that the catalyst of the present invention (Ni2Al3 / Ni catalyst) has more significant catalytic stability than the NiAl3 / Ni catalyst (Comparative Example 2). We tested the hydrogenation of 1,4-butynediol by repeatedly using the catalyst of the present invention, and added about 20% of new catalyst after each cycle. The test results are as follows: Figure 8 As shown, we can Figure 8 It can be seen from the above that the conversion rate of 1,4-butynediol always remained at 100%, and when the catalyst was used for the fourth time in the cycle, 90% of 1,4-butynediol was still converted into 1,4-butanediol; Fig. 9 It can be seen that as the number of cycles of the NiAl3 / Ni catalyst increases, the conversion rate of the NiAl3-Ni catalyst to 1,4-butynediol remains 100%, but the selectivity to 1,4-butanediol decreases significantly, and the second selectivity is 13.3% lower than the first selectivity. When used for the fourth time in the cycle, the selectivity is only 73.6%. It can be seen that the catalytic stability of the catalyst obtained by matching the Ni phase with different nickel-aluminum intermetallic compound phases is fundamentally different. The coordination between the Ni2Al3 phase and the Ni phase of the catalyst of the present invention can further improve the catalytic stability of the catalyst.

[0057] We also found that the catalytic ability of the catalyst for different substances is completely different due to the different combinations of the metal phase and the nickel-aluminum intermetallic compound phase. Fig.10 It can be seen that each catalyst has different catalytic activities for different catalytic products. We believe that this is significantly related to the structure of the catalyst itself; we can verify our conjecture through the conversion rate of 1,4-butynediol by different catalysts and the selection of catalysts in Table 1. It can be seen that the NiAl3-Ni catalyst and the Ni2Al3-Ni catalyst of the present invention have completely different catalytic performance, selectivity and stability due to the different design combinations in the structure, especially the catalytic stability performance of the catalyst.

[0058] How do we design the catalyst of the present invention? What parameters do we need to further control during the preparation process? First, we need to design the precursor before dealloying. Figure 2 and Fig.11 By comparison, it can be seen that Figure 2 is Example 2, and FIG. 12 is Comparative Example 2. Due to the different mass fractions of Ni in the catalyst precursor, the phases in the catalyst obtained will also be different. We can see that Fig.11 In the comparative example 2, when the mass fraction of Ni in the catalyst precursor is 19.5%, after 90 minutes of dealloying, the obtained catalyst is mainly NiAl3 phase; Figure 2 In the catalyst, when the Ni mass fraction in the catalyst precursor is 50%, after 20 minutes of dealloying, the obtained catalyst is mainly Ni2Al3 phase. It can be seen that the Ni / Al atomic ratio in the catalyst precursor has a direct relationship with the selection of the nickel-aluminum intermetallic compound phase in the final catalyst. We further prefer that the Ni mass fraction in the catalyst precursor is 44.3%-55.0%.

[0059] In the precursor of the catalyst within the mass fraction range of Ni of the present invention, we further design the nickel-aluminum intermetallic compound phase and the nickel phase in the catalyst by designing the Ni / Al atomic ratio in the catalyst precursor. By designing the Ni / Al atomic ratio in the catalyst precursor, the molar ratio of the nickel-aluminum intermetallic compound phase and the nickel phase in the catalyst can be further adjusted, as shown in Example 3 and Example 4 and compared, and the results are shown in Table 2. When the mass percentage of Ni in the precursor alloy increases, the nickel-aluminum intermetallic compound phase in the final catalyst obtained increases, and the molar ratio of the nickel phase and the nickel-aluminum intermetallic compound phase in the catalyst also affects the selectivity of the catalyst. We can find that the selectivity of the catalyst obtained in Example 3 and Example 4 for 1,4-butanediol is different, and Example 3 is better. We further prefer that the molar ratio of the Ni phase and the Ni2Al3 phase in the catalyst is 1-2.5.

[0060] We used different concentrations of sodium hydroxide to 31.5 Al 68.5 The alloy was subjected to corrosion experiments, and the results are shown in Figure 12(c). Figure 12 is the LSV curve, from which the corrosion of the material can be seen. When the current in Figure 12 is positive, and the current increases with the increase of voltage, it indicates that the material is corroding, and the voltage corresponding to the current is the corrosion potential; when the corrosion potential is negative, it indicates that the material is corroding freely; when the corrosion voltage is positive, it indicates that the material cannot corrode freely and requires an external voltage to corrode. Figure 12(c) reflects the same Ni 31.5 Al 68.5The corrosion of the alloy in 0.4M and 0.6M sodium hydroxide concentrations. As can be seen from Figure 12(c), both 0.4M and 0.6M sodium hydroxide can corrode Ni 31.5 Al 68.5 Alloy. Among them, Ni 31.5 Al 68.5 The alloy showed two voltage sections in both 0.4M and 0.6M sodium hydroxide solutions, which increased with the increase of current, so corrosion of two phases occurred. When the first phase was corroded, the corrosion potential of this phase was -0.224V in 0.6M NaOH solution, and -0.183V in 0.4M NaOH solution. Free corrosion occurred at this time, and the corrosion potential was smaller in 0.6M sodium hydroxide solution, so 0.6M sodium hydroxide was more likely to corrode the first phase; when the second phase was corroded, the LSV curves in 0.6M NaOH solution and 0.4M NaOH solution were at voltages of 0.203V and 0.189V, respectively, which showed that the corrosion of the second phase was not free corrosion; we also found that the difference between the two corrosion potentials in 0.6M NaOH solution was greater than that in 0.4M NaOH solution, so 0.6M sodium hydroxide was more likely to preserve the relatively inactive Ni2Al3 phase. To this end, we can verify our conjecture through Figure 12 (a) and (b). In Figure 12 (a) and Figure 12 (b), 0.6M sodium hydroxide solution is selected for corrosion, where (a) is NiAl3 phase and (b) is Ni2Al3 phase. From Figure 12 (a), it can be seen that the corrosion potential of NiAl3 phase is -0.5V, and after the corrosion potential, the current is 0, which shows that NiAl3 phase can be freely corroded and NiAl3 phase is completely corroded; and from Figure 12 (b), it can be seen that the corrosion potential of Ni2Al3 phase is -1.5V, which shows that Ni2Al3 phase needs to be pressurized to further corrode, so Ni2Al3 phase can finally stably exist in 0.6M sodium hydroxide solution. This can also verify that in Figure 12 (c), Ni 31.5 Al 68.5 The NiAl3 phase in the alloy is completely corroded, and the Ni 31.5 Al 68.5 The Ni2Al3 phase in the alloy can exist stably. We further prefer that the concentration of sodium hydroxide is 0.6M.

[0061] In summary, the catalyst of the present invention has good catalytic performance, selectivity, catalytic stability, and good stability in air.

[0062] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanoporous nickel-based intermetallic compound catalyst for hydrogenation of 1,4-butynediol, characterized in that: The method comprises the following steps: smelting pure nickel and pure aluminum to obtain a nickel-aluminum alloy ingot, vacuum spinning to obtain a nickel-aluminum alloy strip, obtaining a catalyst precursor, crushing to obtain a nickel-aluminum alloy powder of 80-200 meshes, using 0.4M-0.6M sodium hydroxide to dealloy the nickel-aluminum alloy powder for 20min-120min at 20°C-30°C, washing and drying to obtain the catalyst of the present invention; The nanoporous nickel-based intermetallic compound catalyst prepared by the method contains Ni phase and Ni2Al3 phase; The mass fraction of Ni in the precursor of the catalyst is 43.3%-55.0%; The mass fraction of Ni in the catalyst is 68.5%-76.5%; the molar ratio of Ni phase to Ni2Al3 phase in the catalyst is 1-2.

5.

2. The method for preparing a nanoporous nickel-based intermetallic compound catalyst for hydrogenation of 1,4-butynediol according to claim 1, characterized in that: The catalyst has a nanoporous structure and a specific surface area of ​​70 m 2 / g-120m 2 / g; the average pore size of the nanoporous structure is 4nm-30nm.

3. The method for preparing a nanoporous nickel-based intermetallic compound catalyst for hydrogenation of 1,4-butynediol according to claim 1, characterized in that: The concentration of the sodium hydroxide is 0.6M.

4. A nanoporous nickel-based intermetallic compound catalyst for hydrogenation of 1,4-butynediol, characterized in that: The method is prepared by any one of claims 1 to 3.